Case report: Compound heterozygous mutations in the KDSR gene cause progressive keratodermia and thrombocytopenia - Wu, Li; Zhang, Yajie; Zi, Juan; Yan, Yinyan; Yu, Lihua; Lin, Danna; Huang, Lulu; Lai, Xiaorong; Liao, Xu; Yang, Lihua (Frontiers in Pediatrics, 2022)
KDSR (3-ketodihydrosphingosine reductase) is a short-chain dehydrogenase located in the endoplasmic reticulum. Mutations in KDSR cause defects in ceramides, which play a key role in the biological processes of the skin and other tissues.. Herein, we report a case of compound heterozygous mutations in KDSR that caused progressive keratodermia and thrombocytopenia in a 2-year-old male patient.